Switching patients in the age of long-acting recombinant products?. (14th January 2019) - Escobar, Miguel; Santagostino, Elena; Mancuso, Maria Elisa; Coppens, Michiel; Balasa, Vinod; Taylor, Jason A.; Iorio, Alfonso; Negrier, Claude
ABSTRACT: Introduction : Prophylaxis with factor replacement therapy is the gold standard for the treatment of hemophilia, but this often requires frequent infusions. A number of long-acting factor products have been developed to reduce the burden on patients. Areas covered : This is an overview of information presented at two symposia held at the World Federation of Hemophilia and International Society on Thrombosis and Haemostasis – Scientific and Standardization Committee annual meetings. The pharmacokinetic, safety and efficacy data for long-acting recombinant products are reviewed, with a focus on recombinant factor IX albumin fusion protein (rIX-FP) and rVIII-SingleChain. This overview also provides a guide for managing a patient's switch to long-acting products. Expert opinion : Long-acting products may allow patients to maintain or decrease bleeding rates whilst increasing their dosing interval, which may in turn reduce the burden on patients and caregivers. When switching patients to long-acting products health-care professionals should provide balanced and thorough education to the patient, whilst supporting their emotional well-being. Regimens should address patients' needs and goals but should also be guided by clinical phenotype and pharmacokinetic assessment. Follow-up should assess safety concerns, bleeding rates, joint health and the impact of the regimen on patients' lifestyle.